2021
DOI: 10.1108/tr-07-2020-0343
|View full text |Cite
|
Sign up to set email alerts
|

Overtourism and employment outcomes for the tourism worker: impacts to labour markets

Abstract: Purpose This paper aims to undertake an ideal-typical analysis of the implications of overtourism on employment at the level of the destination. Design/methodology/approach The paper offers a theoretical analysis that uses as a starting point a traditional labour market model to explore the employment implications of a labour demand shock as a result of overtourism at a destination level. Although a theoretical exploration, examples are provided offering empirical support for the theoretical propositions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 76 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…The majority of tomorrow's tourists will likely also include yesterday's overtourists, with the same tastes and desires they had in pre-COVID days but even more impatient to travel after the hiatus of the pandemic. Additionally, increased tourism numbers do not necessarily mean increased jobs and wages (Walmsley et al, 2021). In Iceland, increased demand for tourism was instead met by immigration of labour from regions with lower wages (Wendt et al, 2020) as in Spain also (Can ˜ada, 2018).…”
Section: Inaction On Overtourismmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of tomorrow's tourists will likely also include yesterday's overtourists, with the same tastes and desires they had in pre-COVID days but even more impatient to travel after the hiatus of the pandemic. Additionally, increased tourism numbers do not necessarily mean increased jobs and wages (Walmsley et al, 2021). In Iceland, increased demand for tourism was instead met by immigration of labour from regions with lower wages (Wendt et al, 2020) as in Spain also (Can ˜ada, 2018).…”
Section: Inaction On Overtourismmentioning
confidence: 99%
“…argue that "overtourism is driven by both global and domestic policy factors". Although proponents of a smaller and/or greener form of tourism (Everingham and Chassagne, 2020) argue for significant changes in the whole tourism system, including a reduction in tourist numbers, it sometimes appears forgotten or ignored by such commentators that tourism is an economic activity and that while tourists may engage in the activity for pleasure, those in the supply and support sectors participate for economic gain (Walmsley et al, 2021;Ghoochani et al, 2020). It is generally unrealistic and ineffective to expect those agencies to have much regard for anything beyond their own economic benefit, as their survival will depend on how economically successful they are.…”
Section: Inaction On Overtourismmentioning
confidence: 99%
See 1 more Smart Citation
“…The same can be said about tourism employment. While tourism is often hailed as providing "weaker" groups in society with employment opportunities, Walmsley, Koens, and Milano (2021) note that this is not self-evident. They argue that unfettered tourism growth can lead to lower nominal and real wages, deepen divisions in the labour market, also between local and migrant workers, increase work pressure without sufficient remuneration as well as a deterioration of working conditions.…”
Section: The Future Of Cultural Tourism Revisited: Three Visionsmentioning
confidence: 99%
“…They also found that road transportation promoted service sector employment more than railway and inland water transport. Walmsley, Koens and Milano [ 18 ] have found that overtourism, excessive numbers of tourists in a particular tourist spot, has the potential to impact wage and to divide labor market. In the Indian context, R&D, legal, media and broadcasting services have all been identified as potential sectors for future growth [ 19 ].…”
Section: Background and Literature Reviewmentioning
confidence: 99%